Accuracy assessment of Terrestrial Laser Scanning (TLS), Airborne Light Detection and Ranging (LiDAR), and Interferometric Aperture Synthetic Radar (IfSAR) in agriculture - Daud, R. A. A.; Abdullah, Ahmad Fikri (Faculty of Engineering, Universiti Putra Malaysia, 2016)
Terrestrial Laser Scanner (TLS) is one of the laser scanning technologies used in many applications nowadays. It produces very precise and fast measured 3D data acquisition of an object. This latest technology is very cost-effective and user-friendly. In this study, TLS was used to determine the Digital Elevation Model (DEMs) for Taman Sri Lambak, Kluang, Johor. The DEMS is utilized for the comparison of the, Airborne Light Detection and Ranging (LiDAR), Interferometric synthetic aperture radar (IfSAR), and TLS to ascertain the accuracy of these three different application in generating DEMs. The TLS data was filtered using Progressive Morphology algorithm using open source software, Airborne LiDAR Data Processing Tool (ALDPAT). Airborne LiDAR was filtered using TerraScan while IfSAR is already in raster data output. The DEM of TLS is generated by using Triangulate Irregular Network (TIN) in ArcMAP 10.2 to illustrate the differences of elevation between LiDAR, IfSAR, and TLS. From this assessment, TLS has better accuracy when compared to the benchmark obtained from Jabatan Ukur dan Pemetaan Malaysia (JUPEM) rather than LiDAR and IfSAR.